Laser cladding of Ni50Cr: a parametric and dilution study - Song, B.; Hussain, T.; Voisey, K.T. (Elsevier, 2016)
The increasing use of biomass as a fuel is leading to higher fireside corrosion of the heat exchangers in boilers due to the high chlorine and alkali metal content in the fuel. Laser cladding of Ni50Cr is a promising technique to enhance fireside corrosion resistance of boiler tubes from this aggressive environment. A parametric study is carried out on the blown powder based laser cladding of Ni50Cr on 304 stainless steel. Successful deposits were generated and the effects of the various process parameters on clad geometry and dilution are reported. The various commonly used techniques for determination of clad dilution are compared and some guidelines for their use are suggested.